Educational quality and the impact cof interventions in education in the Caribbean, 1990-1999: An annotated bibliography - Quaminax, AIyejina, Lynda (Office of the UNESCO Representative in the Caribbean, 2000)
This bibliography attempts to provide a comprehensive listing as possible of studies on education in the Caribbean, produced between 1990 and 1999, which address some of the major issues identified at the 1990 World Conference on Education for All, as well as the concerns of the 11th Conference of Commonwealth Ministers of Education (1990). The entries in the bibliography are arranged alphabetically by broad subject areas, subdivided by country/region. It is provided with four indexes: 1) a personal name index, 2) an index of corporate authors and sponsors, 3) a geographic index, and 4) a supplementary subject index.
Keywords: educational quality